2020
DOI: 10.1186/s13568-020-00993-w
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol ameliorates Cisplatin induced nephrotoxicity by modulating oxidative stress, inflammation and apoptosis via ERK and NF-κB pathways

Abstract: Anticancer drug like Cisplatin are associated with serious problem like nephrotoxicity. The effect of Kaempferol is a plant-derived flavonoid compound. The present work evaluated the effect of Kaempferol in mouse model of Cisplatin mediated nephrotoxicity also the involved mechanism. Oxidative stress, kidney function, histology, inflammation, apoptosis, level of proteins, Nrf2 translocation and its effect on cascades such as NF-κB and ERK were studied. It was observed that the pre-treatment of KPF reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…For instance, chrysin offers protection against cisplatin-induced hepatotoxicity and colon toxicity [340]. Luteolin, kaempferol, chrysin, and quercetin also prevent ototoxicity and nephrotoxicity damage induced by cisplatin [340][341][342][343][344][345]. Resveratrol offered protection against cisplatin-induced epididymal toxicity, testicular toxicity, and toxicity in ovarian and cavity cancer cells [346,347].…”
Section: Other Cardiotoxic Cancer Treatments Cisplatinmentioning
confidence: 99%
“…For instance, chrysin offers protection against cisplatin-induced hepatotoxicity and colon toxicity [340]. Luteolin, kaempferol, chrysin, and quercetin also prevent ototoxicity and nephrotoxicity damage induced by cisplatin [340][341][342][343][344][345]. Resveratrol offered protection against cisplatin-induced epididymal toxicity, testicular toxicity, and toxicity in ovarian and cavity cancer cells [346,347].…”
Section: Other Cardiotoxic Cancer Treatments Cisplatinmentioning
confidence: 99%
“…NF-κB is present in the cytoplasm along with IκBα, an inhibitory protein. Previous research has demonstrated that NF-κB is activated by the phosphorylation of IκBα, thereby triggering the expression of genes associated with inflammation ( Wang et al., 2020 ). The activation of NF-κB subsequently induces the expression of proinflammatory cytokines, including nitric oxide synthase (iNOS), COX-2, tumor necrosis factor (TNF-α), interleukin 1 beta (IL-1β), and interleukin-6 (IL-6) ( Rojas et al., 2013 ; Liang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kaempferol can treat cholangiocarcinoma through the PI3K-AKT pathway [24] . Moreover, kaempferol lowers the levels of TP53, which is involved in attenuating apoptosis mediated by Cisplatin [52] . In terms of beta-sitosterol, it is reported to induce MAPK phosphorylation, downregulate the PI3K/Akt, thus promote cell apoptosis and cell death [53] .…”
Section: Discussionmentioning
confidence: 99%